The current use and evolving landscape of nutraceuticals. (January 2022) - Chopra, Avijeet S.; Lordan, Ronan; Horbańczuk, Olaf K.; Atanasov, Atanas G.; Chopra, Ishveen; Horbańczuk, Jarosław O.; Jóźwik, Artur; Huang, Linfang; Pirgozliev, Vasil; Banach, Maciej; Battino, Maurizio; Arkells, Nicolas
Abstract: The nutraceutical market is currently a high-impact multi-billion-dollar industry, and it is anticipated to grow rapidly over the next decade. Nutraceuticals comprise diverse food-derived product categories that have become widespread due to increased consumer awareness of potential health benefits and the need for improved wellness. This targeted review is designed to identify the current global trends, market opportunities, and regulations that drive the nutraceutical industry. Safety and efficacy concerns are also explored with a view to highlighting areas that necessitate further research and oversight. Key drivers of the nutraceutical market include aging populations, consumer awareness, consumer lifestyle, increasing cost of healthcare, and marketing channels. Although some nutraceuticals hold promising preventive and therapeutic opportunities, there is a lack of a universal definition and regulatory framework among countries. Moreover, there is a lack of adequate evidence for their efficacy, safety, and effectiveness, which was even further highlighted during the ongoing coronavirus pandemic. Future prospective epidemiological studies can delineate the health impact of nutraceuticals and help set the scientific basis and rationale foundation for clinical trials, reducing the time and cost of trials themselves. Together, an understanding of the key drivers of the nutraceutical market alongside a consistent and well-defined regulatory framework will provide further opportunities for growth, expansion, and segmentation of nutraceuticals applications. Graphical Abstract: ga1